Afiksasi Bahasa Dayak Kenyah Dialek Lepo Jalan di Desa Budaya Sungai Bawang Kecamatan Muara Badak Kabupaten Kutai Kartanegara - Stevani, Liana Sinta; Mulawarman, Widyatmike Gede; Rijal, Syamsul (Universitas Mulawarman, 2021)
This study aims to describe the form of affixes, affixation (the processof affixing), and the meaning of affixes in the Dayak Kenyah dialect of Lepo’ Jalan in Sungai Bawang Culture Village. This research is a qualitative research. This qualitative descriptive research method was used because: this study explains and describes the form of affixes, affixation (the process of affixing), and the meaning of affixes. Data collection was carried out using the look method with advanced techniques listening engagement technique, speaking involvement free listening technique, recording technique, and note-taking technique. Based on data analysis, the resultof research and discussion can be cocluded (1) there are 11 (eleven)forms of affixes for the Dayak Kenyah dialect of Lepo’ Jalan in Sungai Bawang Cultural Village, (2) affixation (process of affixing)Dayak Kenyah dialect Lepo’ Jalan in Sungai Bawang Cultural Village. The word is formed from two elements, namely affixes that attach of the basic word or basic form so that affixed words are formed, (3) the meaning of affixes for the Dayak Kenyah languange in the Lepo’ Jalan dialect in the Cultural Village Sungai Bawang means doing something, stating an action, stating a situation, making something, and stating information.